The roles of soil macrofauna on litter decomposition of Acacia mangium Willd - MUSYAFA MUSYAFA (Biodiversitas Journal of Biological Diversity, 2005)
Acacia mangium has been widely planted in industrial forest plantation (HTI). High litter accumulation in floor of A. mangium (Acacia) plantation due to slow process of decomposition, may disturb nutrient cycling process. It is also vulnerable to forest fire especially in dry season. The research was aimed to clarify the density of soil macrofauna in Acacia plantation and the roles of macrofauna in the decomposition of Acacia litter. The density of macrofauna was estimated by using pitfall traps and hand-sorting method in Acacia stand, at Wanagama Reaserch Center, Gadjah Mada University (GMU). In the laboratory, Spirobolus sp. (Diplopoda) were fed with the litter of Acacia and the ingestion rate, defecation rate, and assimilatioan rate were determined. C and N content of the litter and feces wereanalyzed at Laboratory of Soil Science, Faculty of Agriculture GMU. The results showed that the density of soil macrofauna was low (74.6 individual/m2). The study in laboratory showed that Spirobolus did not est newly fallen leaves of Acacia. Ingestion rate, defecation rate, assimilation efficiency of millipede fed with partly decomposed Acacia leaves were 76.8 mg/g/day, 7.0 mg/g/day, 6.1 mg/g/day respectively. C/N ratio of feces was lower than that of partly decomposed Acacia leaves. It indicated significant change during gut passage of Spirobolus sp. This millipede should be introduced in Acacia plantation as a potential decomposer.Â© 2005 Jurusan Biologi FMIPA UNS SurakartaKeywords: soil macrofauna, decomposition, ingestion rate, defecation rate, C/N ratio